Role of Public Health Campaigns in Increasing Vaccination Rates in Rural Communities in Bangladesh - Hakim, Abdul (International Journal of Health Sciences, 2025)
Purpose: The aim of the study was to investigate the role of public health campaigns in increasing vaccination rates in rural communities. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Public health campaigns have proven effective in increasing vaccination rates in rural communities, especially when using a combination of media and direct methods like community meetings or mobile health units. Multi-channel approaches, such as multimedia campaigns, have shown significant increases in vaccine uptake by targeting different demographic groups. Community-led educational sessions have also led to notable improvements by leveraging trusted local figures to address myths and encourage immunization. SMS reminders have helped improve adherence to vaccination schedules, though challenges like phone ownership and literacy still exist. Unique Contribution to Theory, Practice and Policy: Health belief model (HBM), diffusion of innovations theory & social ecological model (SEM) may be used to anchor future studies on the role of public health campaigns in increasing vaccination rates in rural communities. It is essential to leverage the power of trusted local figures, such as community leaders, healthcare workers, and teachers, to address vaccine hesitancy. Governments and public health bodies should develop policies that prioritize context-specific, culturally sensitive, and linguistically appropriate campaigns in rural areas.